Legal Nature and Inheritance of Virtual Property in Ukraine and the World: Current Status, Problems, Prospects - Davydova, Iryna; Didenko, Larysa; Tomina, Viktoriya (Ius Humani. Jornal do direito, 2021)
In recent years, there has been a growing interest in such a phenomenon as a digital inheritance. Sooner or later, users of social networks or online games begin to think about the status of their virtual assets, as they become valuable since users have spent a lot of time to earn them. However, legislation on digital inheritance remains either imperfect or does not answer the question of what happens to digital property after one's death. The study aimed to describe the situation in the field of digital inheritance through the concepts of virtual property and IT objects. We used systemic, formal-legal, and hermeneutic methods to describe the state of the art in the area of virtual property and digital inheritance through the lens of jurisprudence. The found results suggest that digital inheritance is a growing problem due to imperfect or absent legislation with simultaneously increasing role and importance of the virtual world and digital assets in everyday life. Accordingly, we have found that court decisions set the tone for the development of the legislative process in this field, but at the moment, we are only at the beginning of the creation of solid and harmonized legislation towards digital inheritance. It is also determined that the concept of virtual property does not contradict the general principles of civil law, so it can be applied in the context of digital inheritance.